2018
DOI: 10.1371/journal.pone.0201548
|View full text |Cite
|
Sign up to set email alerts
|

Admission prevalence of colonization with third-generation cephalosporin-resistant Enterobacteriaceae and subsequent infection rates in a German university hospital

Abstract: BackgroundMany patients admitted to a hospital are already colonized with multi-drug resistant organisms (MDRO) including third-generation cephalosporin-resistant Enterobacteriaceae (3GCREB). The aim of our study was to determine the prevalence of rectal 3GCREB colonization at admission to a large German university hospital and to estimate infection incidences. In addition, risk factors for 3GCREB colonization were identified.Materials/MethodsIn 2014 and 2015, patients were screened for rectal colonization wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
3
13
0
2
Order By: Relevance
“…Data from targeted admission screenings in Switzerland are comparable to numbers in Germany, where similar carriage rates among patients transferred from abroad for resistant Gram-negatives (13% vs. 14-17% in our review) and for MRSA (4% vs. 1-4% in our review) were found [6]. ESBL-prevalence from universal admission screening was 8% in a study included in our review, which is comparable to the 10% prevalence found in a German study [9,59]. One of the most urgent antibiotic resistant threats, coming along with increased morbidity and mortality in infected patients, are CPE [60].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Data from targeted admission screenings in Switzerland are comparable to numbers in Germany, where similar carriage rates among patients transferred from abroad for resistant Gram-negatives (13% vs. 14-17% in our review) and for MRSA (4% vs. 1-4% in our review) were found [6]. ESBL-prevalence from universal admission screening was 8% in a study included in our review, which is comparable to the 10% prevalence found in a German study [9,59]. One of the most urgent antibiotic resistant threats, coming along with increased morbidity and mortality in infected patients, are CPE [60].…”
Section: Discussionsupporting
confidence: 84%
“…1–4% in our review) were found [6]. ESBL-prevalence from universal admission screening was 8% in a study included in our review, which is comparable to the 10% prevalence found in a German study [9, 59]. One of the most urgent antibiotic resistant threats, coming along with increased morbidity and mortality in infected patients, are CPE [60].…”
Section: Discussionsupporting
confidence: 70%
“…Diabetes has previously been identified as a potential risk factor for MDRO colonization [36,37] and subsequent bloodstream infections with intestinal bacteria due to disruption of the gut barrier [38,39]. The overall prevalence of MDRO colonization at admission has been reported to be as high as 10% for ESBL producing Enterobacterales [40,41], reaching a prevalence of 20% in specific patient subgroups [9], and 2% for VRE [42] in German tertiary care centers. The colonization rate in our study was slightly lower than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of MRSA are known to have an increased risk of subsequent symtomatic infection (Van Belkum and Verbrugh 2001;Nelson et al 2018), whereas the risk of subsequent symtomatic infection in gut carriers of MDRGN is largely unkown (Turbett and Mansour 2016;Rottier et al 2015;Goulenok et al 2013;Boldt et al 2018). Recent reports indicate a very low frequency of subsequent symtomatic infection in a large unselected patient group of gut carriers (Lindblom et al 2018;Boldt et al 2018). 10 This is particularly salient since identification of an MDR carrier status increases the risk of broad-spectrum antibiotic overuse, which may have negative consequences for both individual and society.…”
Section: Epidemiological Comparison Mrsa Vs Mdrgnmentioning
confidence: 99%